The Likelihood Ratio Test in Structural Equation Models: A Multi-Group Approach to Portuguese Material Deprivation - Paula C.R. Vicente (International Journal of Engineering and Management Research, 2018)
In this study a multi-group approach is used within the structural equations modelling framework, with the purpose of validating the temporal stability of the material deprivation measurement model, as well the impact of the existence of children in the household. For the purposes of model comparison, the use of the likelihood ratio test is discussed, when the normal distribution of the data cannot be assumed and the robust Satorra-Bentler scaled-corrected chi-square estimator is used. The statistical package LISREL 8.8 is used for estimating models.